INSP-06. Recent advances in improving neuropsychological outcomes for paediatric brain tumour patients - Are we entering a new era?. (3rd June 2022) - Mabbott, Donald
Abstract: Children and youth treated for brain tumours can sustain a brain injury as a consequence of the tumour and curative therapy leaving them with significant cognitive challenges. Advances in treatment for paediatric brain tumours – particularly the delivery of radiotherapy – have been associated with improved neuropsychological outcome in survivors, however. This presentation will first focus on work documenting the impact of changes in cranial radiotherapy delivery and modality on neuropsychological late effects in children treated for medulloblastoma. Outcomes in patients treated on modern protocols are substantially improved relative to prior therapy, however challenges remain. Second, novel approaches for cognitive recovery and brain repair in survivors of paediatric brain tumours will be discussed, with a focus on novel approaches for fostering endogenous neuroplasticity for cognitive recovery and brain repair in children and youth treated for paediatric brain tumours.